2015
DOI: 10.1155/2015/934065
|View full text |Cite
|
Sign up to set email alerts
|

Liver Failure Impairs the Intrahepatic Elimination of Interleukin-6, Tumor Necrosis Factor-Alpha, Hepatocyte Growth Factor, and Transforming Growth Factor-Beta

Abstract: The strategic location of the liver and its metabolic activity make it a key organ regulating homeostasis. Our purpose was to examine its participation in removal of cytokines: interleukin-6 (Il-6), tumor necrosis factor-alpha (TNF-α), hepatocyte growth factor (HGF), and transforming growth factor-beta (TGF-β) from the portal circulation in human. 20 liver donors and 20 patients with end-stage liver failure were included in the study. Their blood was collected during liver transplantation from the portal, hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…However, few studies investigated the effect of TPE and DPMAS on serum levels of IL‐6 in ACLF patients. Our results showed that serum IL‐6 was consistently increased after both TPE and DPMAS, which may be due to increased production and impaired elimination rates of IL‐6 in HBV‐ACLF patients, higher than removal rates by TPE and DPMAS.…”
Section: Discussionmentioning
confidence: 65%
“…However, few studies investigated the effect of TPE and DPMAS on serum levels of IL‐6 in ACLF patients. Our results showed that serum IL‐6 was consistently increased after both TPE and DPMAS, which may be due to increased production and impaired elimination rates of IL‐6 in HBV‐ACLF patients, higher than removal rates by TPE and DPMAS.…”
Section: Discussionmentioning
confidence: 65%
“…TGFβ1 possesses a wide range of biological functions, such as suppression of the proliferation of gingival epithelial cells (29,30), early embryogenesis (31) and hematopoiesis (32), apoptosis of gingival epithelial cells, and formation of the junctional epithelium (33). Apoptosis can occur through three major pathways: the mitochondrial pathway, the Fas cell surface receptor pathway, and endoplasmic reticulum stress (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in our experimental setup we used TNF concentrations that can be detected in different areas of the liver vasculature network (3–10 ng/ml) under physiological and pathological conditions (Porowski et al, 2015 ). However, under some conditions, such as non-alcoholic steatohepatitis (NASH) or after liver transplantation much higher TNF levels may be measurable (34.2 and 43 ng/ml, respectively).…”
Section: Discussionmentioning
confidence: 99%